Depression during pregnancy and the risk of low birth weight, preterm birth and intrauterine growth restriction- an updated meta-analysis - Ghimire, Upama; Papabathini, Shireen Salome; Kawuki, Joseph; Obore, Nathan; Musa, Taha Hussein (Early human development, 2021)
Depression during pregnancy is a significant cause of adverse birth outcomes, and its prevalence has increased in recent years. This study aimed to give an updated quantification of the risk of preterm birth (PTB), low birth weight (LBW) and intrauterine growth restriction (IUGR) that is associated with antenatal depression. The search was done in different databases, including Web of Science, Scopus and PubMed, from January 2010 to March 2020, and only English-language articles were considered. We only included studies that assessed depression during pregnancy and those that reported data on antenatal depression with at least one adverse birth outcome (PTB, LBW, or IUGR). The quality of studies was assessed using an adaptation of the Newcastle-Ottawa scale assessment tool. The analysis was conducted using STATA (version 12), pooled effect sizes were calculated using the random-effects model and heterogeneity was tested for using the I2 statistic. The analysis included 23 studies of PTB, LBW and IUGR. There was a significant risk of PTB (RR = 1.35, 95% CI 1.19–1.52), LBW (RR = 1.86, 95% CI 1.32–2.62) and IUGR (RR = 4.39, 95% CI 2.45–7.86). Control for confounders, time of assessing depression, among others altered the risk of LBW due to depression. In addition, depressed women in developing countries had a higher risk of PTB (RR = 2.07, 95% CI 1.13–3.81). This study identifies a significant risk of PTB, LBW and IUGR due to antennal depression and recognises a need for targeted preventive interventions such as prompt screening to improve and promote maternal mental health care. •There is a significant risk of PTB, LBW, and IUGR due to Perinatal Depression.•Risk of LBW was higher when depression was measured in first trimester.•There was a two-fold increase in the risk of PTB due to antenatal depression in developing countries compared to developed countries.